Transformation and Legitimation in Post-apartheid Universities Reading Discourses from 'Reitz' - van der Merwe, J.C (UJ Press, 2016)
Two decades after the democratic transition, South African universities are in turmoil. Whilst the old is slowly becoming unhinged, reimagining the new is protracted and contested. The challenges ahead, including a funding crunch, are formidable and bear the imprint of South African postcolonial specificities and global transformations in higher education. At this moment, critical and engaged socio-historical scholarship is indispensable. Transformation and Legitimation in Post-apartheid Universities: Reading discourses from Reitz is such a work. Revisiting the notorious Reitz incident of 2008, when a satirical video made by students from the University of the Free State (UFS) to register their resistance to the racial integration of black' students into historically white' residences became public, the text offers an analysis of the broader cultural and socio-political context that constituted the conditions of possibility for the incident and its aftermath. Attention is shifted from the principal actors in the original drama a handful of students and workers to a critical interrogation of the broader structures, positions, discourses and practices that fed into the Reitz incident', reaching into the present with violent and racially-charged student and worker protests in 2016. Van der Merwe and Van Reenen deliver a theoretically-rich analysis of the anatomy of current contestations about race and transformation in higher education in South Africa, the resultant legitimation crisis facing the UFS and SouthÂ African universities more generally, as well as ways to restore institutional legitimacy and reputation, focusing on instituting deeper, more durable change that unlocks the promise of democracy. Dr Irma du Plessis University of Pretoria